Characteristics, Treatment Complexity, and Outcome of Mixed-Phenotype Acute Leukemia in Children in a Low–Middle-Income Country - Salama, Maram; Ahmed, Sonia; Soliman, Sonya; El-Sharkawy, Nahla; Salem, Sherine; El-Nashar, Amr; Khedr, Reham; Lehmann, Leslie; Sidhom, Iman; El-Haddad, Alaa (Frontiers in Oncology, 2022)
Background: Mixed phenotype acute leukemia (MPAL) in children is an uncommon subtype of acute leukemia that cannot be definitively assigned to a specific lineage. There is no consensus on the best approach to therapy. Management is further complex in low-middle-income countries (LMICs). Aim: To evaluate the clinicopathological characteristics as well as outcomes of patients with MPAL in a developing country. Patients and methods: A retrospective descriptive study of 42 pediatric patients newly diagnosed with MPAL from July 2007 until December 2017. Results: The immunophenotyping was T/Myeloid in 24 patients (57.1%) and B/Myeloid in 16 (38.1%). Three subjects had MLL gene rearrangement, two had Philadelphia positive chromosomes, and eight had FLT3-ITD with a ratio >0.4. Two subjects died before starting chemotherapy. Ten patients (25%) received ALL induction, and all achieved complete remission (CR) with no induction deaths and no shift of therapy. Thirty patients (75%) started therapy with AML induction: five (16.6%) died during induction, 17 (56.7%) achieved CR, and 10 patients received maintenance ALL therapy after ending AML treatment. Four of the eight patients with induction failure were switched to ALL therapy. The 5-year event-free (EFS), as well as overall survival (OS), were 56.7% (standard error [SE]: 8.1%) and 61% (SE: 8%), while the cumulative incidence of relapse was 21.7% (SE: 6.7%), with a median follow-up duration of 5.8 years. Patients treated with ALL directed therapy had a 5-year EFS of 70% (SE: 14%) and OS of 78.8% (SE: 13%). FLT3-ITD mutation showed a significantly lower five-year-EFS of 28.6% (SE: 17%) versus 75% (SE: 9%) for the wild-type, P= .032. Undernourished patients with a BMI z-score -2 at presentation had a significantly lower 5-year EFS of 20% (SE: 17%) compared to 61.8% (SE: 8%) for patients with BMI z-score > -2, p=0.015 Conclusion: This study supports ALL directed therapy for pediatric MPAL in a setting of LMIC. Given the poor outcome of FLT3-ITD, the role of FLT3 inhibitor needs to be explored in this subset of cases.